The dense indumentum with its polyphenol content may replace the protective role of the epidermis in some young xeromorphic leaves - Karabourniotis, George; Fasseas, Costas (Canadian Journal of Botany, 1996)
The bright, yellow-green, ammonia-induced fluorescence of polyphenol compounds contained in the nonglandular hairs and within the epidermis of Olea europaea and Quercus ilex leaves was age dependent. Epifluorescence microscopic examination of transverse sections of leaves from both species showed that abaxial and adaxial epidermal layers emitted the characteristic green-yellow bright fluorescence only in late developmental stages, when a considerable decrease of the trichome density had already occurred. At earlier developmental stages, only the dense and thick trichome layer emitted the bright green-yellow fluorescence. In addition, the trichomes of young leaves of Olea and Quercus resembled the glandular ones of other species morphologically and possibly functionally. These findings suggest that the protective role of the trichome against ultraviolet-B radiation damage and (or) other environmental factors is particularly significant during the early stages of leaf development and may be less important at later stages, when the protective role is taken over by the epidermis. Keywords: leaf hairs, phenolics, UV-B radiation damage, leaf development, Olea europaea L., Quercus ilex L.
doi: 10.1139/b96-043
Keywords: leaf development; leaf hairs; Olea europaea L.; phenolics; Quercus ilex L.; UV-B radiation damage

The dense indumentum with its polyphenol content may replace the protective role of the epidermis in some young xeromorphic leaves - Karabourniotis, George; Fasseas, Costas (Canadian Journal of Botany, 1996)
The bright, yellow-green, ammonia-induced fluorescence of polyphenol compounds contained in the nonglandular hairs and within the epidermis of Olea europaea and Quercus ilex leaves was age dependent. Epifluorescence microscopic examination of transverse sections of leaves from both species showed that abaxial and adaxial epidermal layers emitted the characteristic green-yellow bright fluorescence only in late developmental stages, when a considerable decrease of the trichome density had already occurred. At earlier developmental stages, only the dense and thick trichome layer emitted the bright green-yellow fluorescence. In addition, the trichomes of young leaves of Olea and Quercus resembled the glandular ones of other species morphologically and possibly functionally. These findings suggest that the protective role of the trichome against ultraviolet-B radiation damage and (or) other environmental factors is particularly significant during the early stages of leaf development and may be less important at later stages, when the protective role is taken over by the epidermis. Keywords: leaf hairs, phenolics, UV-B radiation damage, leaf development, Olea europaea L., Quercus ilex L.
doi: 10.1139/b96-043doi: 10.1139/b96-043The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: leaf development; leaf hairs; Olea europaea L.; phenolics; Quercus ilex L.; UV-B radiation damage